Model validity of randomised placebo-controlled trials of individualised homeopathic treatment. Issue 3 (July 2015) - Mathie, Robert T.; Van Wassenhoven, Michel; Jacobs, Jennifer; Oberbaum, Menachem; Roniger, Helmut; Frye, Joyce; Manchanda, Raj K.; Terzan, Laurence; Chaufferin, Gilles; Dantas, Flávio; Fisher, Peter
<x xml:space="preserve">Abstract</x> Background Though potentially an important limitation in the literature of randomised controlled trials (RCTs) of homeopathy, the model validity of homeopathic treatment (MVHT) has not previously been systematically investigated. Objective As an integral part of a programme of systematic reviews, to assess MVHT of eligible RCTs of individualised homeopathic treatment. Methods From 46 previously identified papers in the category, 31 papers (reporting a total of 32 RCTs) were eligible for systematic review and were thus the subject of the study. For each of six domains of assessment per trial, MVHT was judged independently by three randomly allocated assessors from our group, who reached a final verdict by consensus discussion as necessary. Results Nineteen trials were judged overall as 'acceptable' MVHT, nine as 'uncertain' MVHT, and four as 'inadequate' MVHT. Conclusions These results do not support concern that deficient MVHT has frequently undermined the published findings of RCTs of individualised homeopathy. However, the 13 trials with 'uncertain' or 'inadequate' MVHT will be a focus of attention in supplementary meta-analysis. New RCTs of individualised homeopathy must aim to maximise MVHT and to enable its assessment through clear reporting.